Doe analysis of the influence of sand size and pouring temperature on porosity in LFC - Sudin, Izman (2012)
Lost foam casting is a relatively new process in commercial terms and is widely used to produce defect free castings owing to its advantages like producing complex shape and acceptable surface finish. In the present research, experimental investigations in lost foam casting of aluminium-silicon cast alloy, LM6, were conducted. The main objective of the study was to evaluate the effect of different sand sizes and pouring temperatures on the porosity of thin-wall castings. A stepped pattern was used in the study and the focus of the investigations was at the thinnest 3 mm section. A full 2-level factorial design experimental technique was employed to plan the experiment and subsequently identify the significant factors which affect the casting porosity. The result shows that increasing in the pouring temperature decreases the porosity in the thin-wall section of casting. Finer sand size is more favourable than coarse size for LFC mould making process.